Polysaccharide-based nanocomplexes for co-encapsulation and controlled release of 5-Fluorouracil and Temozolomide - Di Martino, Antonio; Pavelkova, Alena; Maciulyte, Sandra; Budriene, Saulute; Sedlarik, Vladimir (European journal of pharmaceutical sciences, 2016)
Polysaccharide-based nanocomplexes, intended for simultaneous encapsulation and controlled release of 5-Fluorouracil (5-FU) and Temozolomide (TMZ) were developed via the complexation method using chitosan, alginic and polygalacturonic acid. Investigation focused on the influence of polysaccharides on the properties of the system and amelioration of the stability of the drugs, in particular TMZ. The dimensions of particles and their ζ-potential were found to range between 100 and 200nm and -25 to +40mV, respectively. Encapsulation efficiency varied from 16% to over 70%, depending on the given system. The influence of pH on the release and co-release of TMZ and 5-FU was evaluated under different pH conditions. The stability of the loaded drug, in particular TMZ, after release was evaluated and confirmed by LC-MS analysis. Results suggested that the amount of loaded drug(s) and the release rate is connected with the weight ratio of polysaccharides and the pH of the media. One-way ANOVA analysis on the obtained data revealed no interference between the drugs during the encapsulation and release process, and in particular no hydrolysis of TMZ occurred suggesting that CS-ALG and CS-PGA would represent interesting carriers for multi-drug controlled release and drugs protection.
Keywords: Antineoplastic Agents, Alkylating; Drug Compounding; Hexuronic Acids; prekurzory léčiv; Nanoparticles; Prodrugs; dakarbazin; Alginates; nanočástice; fixní kombinace léků; kyselina glukuronová; alkylační protinádorové látky; pektiny; kyseliny hexuronové; Antimetabolites, Antineoplastic; Drug Combinations; příprava léků; Drug Liberation; Chitosan; Drug Stability; stabilita léku; Delayed-Action Preparations; Dacarbazine; Pectins; protinádorové antimetabolity; fluoruracil; uvolňování léčiv; chitosan; Glucuronic Acid; léky s prodlouženým účinkem; Fluorouracil; nosiče léků; algináty; Drug Carriers